Fresh Insights Using Ardl Bound Testing Approach and Analysis of Public Economic Growth Affecting Environmental Quality in Indonesia - Rulinawaty Rulinawaty (Politeknik APP Jakarta, 2022)
The primary purpose of this research is to testify Environmental Kuznets Curve-EKC hypothesis for the economy of Indonesia. ADF and PP unit root tests confirmed the mixed order of integration in the model based on the time-series.data,spanning over 1990 to 2016. Furthermore, the result of ARDL – Long-run confirmed the presence of the EKC hypothesis for the Indonesian economy. In the short run, not an inverted U-shaped relationship has been observed between growth and energy. ECM and bond test verified the existence of cointegration in the model while CUSUM and CUSUM square with other model diagnostics confirmed that the model is the best fit. Based on the results of the analysis, it can be concluded that short & long run dynamic association amongst CO2 Carbon Dioxide, consumption of the energy, urban populations, and the economic development in Indonesia have been examined in this research.